Transformation of Audit and Compliance Management through Robotic Process Automation: A Case Analysis of Deutsche Bank - Nelly Reinalda Sidabutar; Yuli Anra Damanik; Iskandar Muda (Indonesia Economic Journal, 2025)
This article analyzes the transformation of audit and compliance functions through the implementation of Robotic Process Automation (RPA) at Deutsche Bank as part of its broader initiative to modernize business processes and meet increasingly complex regulatory requirements. Using Britton’s process management framework and empirical evidence from reputable international journals, the study evaluates the role of RPA in enhancing operational efficiency, expanding audit coverage, and strengthening the effectiveness of internal control systems. Rule-based automation enables consistent data processing, improves the quality of audit evidence, and accelerates compliance reporting. Furthermore, this research highlights that digital transformation through RPA requires not only technological capability but also strategic alignment, workforce readiness, and robust governance structures. The findings demonstrate that RPA implementation at Deutsche Bank reduces manual errors, increases reporting transparency, and supports continuous auditing and real-time compliance monitoring.